The Investigation of Symptoms and Therapy Delay in Children with Cancer During the Coronavirus 2019 Pandemic: A Single-Center Experience - Yilmaz, Yasin; Tanyildiz, Gülşah; Sahin, Sifa; Eryilmaz, Cansu Ceren; Bilici, Mustafa; Karaman, Serap; Tugcu, Deniz; Unuvar, Aysegul; Karakas, Zeynep (Cerrahpaşa Medical Journal, 2023)
Objective: The coronavirus 2019 pandemic had a worldwide effect on people as well as on pediatric patients with cancer. This effect also caused cancer therapy plan alterations. In this study, we aimed to investigate pediatric patients with cancer who were diagnosed as having coronavirus 2019 infections and the alterations in treatment plans. Methods: Pediatric patients with cancer who were followed up in Istanbul Medical Faculty Pediatric Hematology and Oncology Outpatient Clinic and were diagnosed as having coronavirus 2019 between March 2020 and March 2022 were retrospectively analyzed. Results: A total of 28 patients were diagnosed as having a coronavirus 2019 infection. Forty-three percent of the patients had leukemia, and 57% had solid tumors. More than half (58%) of the patients had mild coronavirus 2019 symptoms. Sixteen (57%) patients had a therapy delay because of coronavirus 2019 infections. The mean therapy delay day was 5.8 ± 2.9 (median: 5 days). Hematologic malignancy (leukemia) had a delay rate of 33% in therapy, and it was 75% in solid tumors. Conclusion: The coronavirus 2019 pandemic affected all people as well as pediatric patients with cancer. The rate of delay in therapy was 57% in our overall pediatric cancer population. The prevention of patients against virus, vaccination of parents, and review of therapy plans might be scheduled in cancer centers. Cite this article as: Yilmaz Y, Tanyildiz G, Sahin S, et al. The investigation of symptoms and therapy delay in children with cancer during the coronavirus 2019 pandemic: A single-center experience. [published Early View Article, 2023 November 30] Cerrahpaşa Med J.; 10.5152/cjm.2023.23008. DOI: 10.5152/cjm.2023.23008.